Experimentally validated analytical modeling of diesel exhaust HC emission rate - Elmoselhy, Salah A.M.; Faris, Waleed Fekry; A. Rakha, Hesham (Engineering: Mechanical Engineering, 2014)
Supercharged diesel engines are a key source of hazardous regulated emissions that have been extensively modelled, yet without explainable mathematical trends. The present paper demonstrates the analytical modeling of the percentage of unburned Hydrocarbon and the HC emission rate in four-stroke diesel engines for trucks. The study presents as well the analytical modeling of the supercharged air density. A sensitivity analysis has been conducted on these developed models. The study shows that the average percentage of deviation of the simulated results from the corresponding freeway cycles field data on the percentage of unburned Hydrocarbon and the HC emission rate is 10.6% and 4%, respectively. The corresponding coefficient of determination is 70% and 83%, respectively. The relative error of the developed models of the percentage of unburned Hydrocarbon and the HC emission rate is 10.6% and 2%, respectively. The study demonstrates with 99% coefficient of determination that the average percentage of deviation of the simulated results from the corresponding field data under the steady speed operating condition for all freeway cycles on the supercharged air density is 3.7%. The relative error of the developed model of the supercharged air density is 4%. These values of relative error are in an order of magnitude of deviation that is less than that of widely recognized models in the field of vehicle powertrain modeling, such as the CMEM. These developed analytical models serve as widely valid models that follow entirely from the principles of physics and the results of these developed models have explainable mathematical trends. The fact that these developed models are dimensionally correct further supports the validity of these models. The present models can help in better analyzing the performance of diesel engines and in developing and assessing the performance of these engines. © 2014, The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.